Mental Health in the Psychology and Tasawuf Perspectives - Nunis Fitria (Jurnal Iman dan Spiritualitas, 2023)
Mental health is essential to learn because it is the well-being of a person's condition in knowing and developing someone’s potential. Because it is considered an important issue, mental health is ultimately correlated with other sciences. One of them is the science of Sufism. The science of Sufism is very appropriate in discussing this mental health problem because the object of study in Sufism and psychology both discuss the human soul. Sufism is well known, and the science that examines mental health is the science of psychology. Combining knowledge between these two branches of knowledge, hoped that it can increase faith to achieve the goal of life, namely, to be happy and prosperous both in this world and in the hereafter.